Photomechanical Response of Pre‐strained Azobenzene‐Functionalized Polyimide Materials. Issue 11 (4th October 2012) - Lee, Kyung Min; Wang, David H.; Koerner, Hilmar; Vaia, Richard A.; Tan, Loon‐Seng; White, Timothy J.; Lendlein, Andreas
Abstract Recently, we have reported that azobenzene‐functionalized polyimide materials exhibit a substantial increase in photogenerated stress in comparison to azobenzene‐functionalized acrylate‐based liquid crystal polymer networks. Here, we show that pre‐straining the azo‐CP2‐20 material further increases the magnitude of the photomechanical response visualized as bending in the cantilever geometry as well as in direct measurements of photogenerated stress. Additionally, we also report on the ability to optically fix both optically and mechanically generated shapes in azo‐CP2‐20. The optically fixable shape memory of azo‐CP2‐20 is enabled by the introduction of excess free volume during thermal processing as the material was pre‐strained.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>